2020
DOI: 10.3390/molecules25102416
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation as a Method of Abiotic Elicitation Improving the Health-Promoting Properties of Plant Products—A Review

Abstract: In this review, the primary objective was to systematize knowledge about the possibility of improving the health-promoting properties of raw plant products, defined as an increase in the content of bioactive compounds, by using ozone. The greatest attention has been paid to the postharvest treatment of plant raw materials with ozone because of its widespread use. The effect of this treatment on the health-promoting properties depends on the following different factors: type and variety of the fruit or vegetabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 170 publications
0
32
0
Order By: Relevance
“…The main non-enzymatic antioxidants include ascorbic acid, polyphenols, carotenoids and anthocyanins, while enzymatic antioxidants include superoxide dismutase (SOD), peroxidases (in the ascorbate-APX, glutathione-GPX forms) and catalase. All of these antioxidants enable plant cells to scavenge ROS and help to prevent cellular damage [ 119 ]. In this regard, Chen et al [ 98 ] investigated the metabolic activity of some antioxidant enzymes found in fresh-cut green peppers including POD, SOD and PAL activities (that were induced by ozone supplied at 6.42 mg cm −3 for 15 min and stored under MAP conditions at 5 °C for 21 days) and PPO activity (inhibited by ozone and MAP treatment).…”
Section: Ozone Treatments and Fresh-cut Fruits And Vegetables Qualitymentioning
confidence: 99%
“…The main non-enzymatic antioxidants include ascorbic acid, polyphenols, carotenoids and anthocyanins, while enzymatic antioxidants include superoxide dismutase (SOD), peroxidases (in the ascorbate-APX, glutathione-GPX forms) and catalase. All of these antioxidants enable plant cells to scavenge ROS and help to prevent cellular damage [ 119 ]. In this regard, Chen et al [ 98 ] investigated the metabolic activity of some antioxidant enzymes found in fresh-cut green peppers including POD, SOD and PAL activities (that were induced by ozone supplied at 6.42 mg cm −3 for 15 min and stored under MAP conditions at 5 °C for 21 days) and PPO activity (inhibited by ozone and MAP treatment).…”
Section: Ozone Treatments and Fresh-cut Fruits And Vegetables Qualitymentioning
confidence: 99%
“…It is very difficult to compare the effects, particularly in a situation when different conditions and different varieties of a given species were used. Moreover, attempts to assess effectiveness of ozonation are additionally hampered by the fact that some researchers do not present detailed information about the conditions, variations, and varieties [22]. Matłok et al [23] performed fumigation of red-veined sorrel plants with 1 ppm ozone and identified significant changes in antioxidant potential on the first and fourth days following treatment.…”
Section: Antioxidant Activity and Bioactive Compounds Contentmentioning
confidence: 99%
“…The ozonation process is a promising method of extending the shelf life of berries (Botondi et al, 2015;Carbone & Mencarelli, 2015;Horvitz & Cantalejo, 2014;Jaramillo-Sánchez et al, 2019;Piechowiak et al, 2020a). Ozone, as a substance with strong antimicrobial properties, reduces the level of microorganisms developing on the fruit during storage, oxidizes the released ethylene, and under appropriate process conditions inhibits adverse changes in the level of antioxidants (Ong et al, 2013;Piechowiak et al, 2019a;Sachadyn-Król & Agriopoulou, 2020). In our previous research, we have proved that ozonation of highbush blueberry fruit with gas at a concentration of 15 ppm for 30 min, every 12 h for 28 days of cold storage, inhibits the growth of mesophilic aerobic bacteria and fungi, including Botrytis cinerea mold during storage (Piechowiak et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%